2021
DOI: 10.1016/j.jamcollsurg.2020.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Single Institution Trial Comparing Whole Blood vs Balanced Component Therapy: 50 Years Later

Abstract: BACKGROUND: Early close ratio transfusion with balanced component therapy (BCT) has been associated with improved outcomes in patients with severe hemorrhage; however, this modality is not comparable with whole blood (WB) constituents. We compared use of BCT vs WB to determine if one yielded superior outcomes in patients with severe hemorrhage. We hypothesized that WB would lead to reduced in-hospital mortality and blood product volume if given in the first 24 hours of admission. STUDY DESIGN: This was a 1-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 39 publications
1
34
1
Order By: Relevance
“…It is interesting that 51% of the centers that use LTOWB would administer RhD‐positive LTOWB to females of childbearing potential whose RhD‐type is either negative or unknown at the time of the transfusion. Perhaps this reflects the adoption of the findings of studies that demonstrated a survival benefit when blood products were administered early in the resuscitation, 6–9 that there are emerging data showing some benefits of transfusing LTOWB, 21–24 and a recognition that hemolytic disease of the fetus and newborn, while still a stressful and emotionally draining diagnosis, is now largely a manageable condition in many parts of the world 25–28 …”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that 51% of the centers that use LTOWB would administer RhD‐positive LTOWB to females of childbearing potential whose RhD‐type is either negative or unknown at the time of the transfusion. Perhaps this reflects the adoption of the findings of studies that demonstrated a survival benefit when blood products were administered early in the resuscitation, 6–9 that there are emerging data showing some benefits of transfusing LTOWB, 21–24 and a recognition that hemolytic disease of the fetus and newborn, while still a stressful and emotionally draining diagnosis, is now largely a manageable condition in many parts of the world 25–28 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have analyzed the frequency of occurrence of clinical outcomes other than mortality following LTOWB transfusion in trauma patients. In two studies, receipt of a median (IQR) of 1 (1–1) and 2 (1–3) LTOWB units, respectively, 12,13 was associated with either no difference in the frequencies of the measured clinical events, or in some cases significantly reduced major complications, such as acute kidney injury, acute respiratory distress syndrome (ARDS), deep vein thrombosis/pulmonary embolism, cardiac arrest, pneumonia, sepsis etc. compared to recipients of CCT.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the data that were generated on the use of LTOWB surrounded implementation strategies in the pre‐hospital and in‐hospital phases of the resuscitation, 1–3 as well as data on the serological safety of transfusing LTOWB to non‐group‐O recipients 4–6 . As the use of LTOWB began to increase in the US and in other countries, 7–9 several studies have attempted to determine whether the use of LTOWB in trauma resuscitation resulted in a survival benefit compared with the transfusion of conventional components (CCT) using different study methodologies and have found conflicting results 10–15 . For example, in a single‐center analysis of 198 injured LTOWB patients who received a median of one unit either pre‐hospital or early in their in‐hospital course, 30‐day mortality was reduced in a multivariate logistic regression model compared to 152 conventional component recipients 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been multiple studies comparing LTOWB to component therapy that have sought to demonstrate the potential benefits of LTOWB with varying results. These studies have used different methodologies and varying doses of WB 10‐15 . A 2020 review of WB studies concluded that there is substantial evidence that WB is safe and feasible, but it has not been shown to be superior to component therapy in any large or randomized studies 16 .…”
mentioning
confidence: 99%